Calculating hole size and crack length in multi-wall systems following an orbital debris impact. (November 2017) - Schonberg, William P.; Williamsen, Joel E.
Highlights: All spacecraft are subject to damage from on-orbit impacts by micro-meteoroids and orbital debris particles. Typical shielding consists of a "bumper" that stands off from the main wall of the spacecraft. The calculation of hole size and crack length following an on-orbit impact is a key element of spacecraft risk assessments. We present the development of a new hole diameter equation and a new crack length equation. These new equations are no longer dependent on the parameters of any ISS module wall configuration, and allow consideration of non-spherical projectile impacts. Abstract: All spacecraft are subject to damage from on-orbit impacts by micro-meteoroids and orbital debris particles. Typical shielding consists of a "bumper" that stands off from the main "inner wall" of the spacecraft element. Because the calculation of the size of the hole and the length of the crack that would occur in a module wall following a perforating on-orbit impact is a key ingredient in the risk assessment process of any spacecraft, it is important to correctly and accurately calculate those quantities. In two previous studies, empirical hole diameter and crack length equations were developed for the thirteen common ISS module wall configurations. In this paper we present the development of a single hole diameter equation and a single crack length equation that would unify the thirteen independent hole diameter and crack length equations developed previously. The advantages of these new equations over those developed previously are that they (1) are no longer tied to or dependent on the parameters of any single ISS module wall configuration, and (2) allow the consideration of the impact of non-spherical projectiles on multi-wall systems. We also clarify some issues with respect to the original thirteen hole diameter and crack length equations as originally presented.